Haraldr Sigurðarson’s arrival in Rus’ and his participation in the campaign against Poland in 1031 - Maciej Lubik (Historisk Tidsskrift, 2020)
In 1031, Haraldr Sigurðarson, also known as harðráði, started his mercenary career, soon becoming one of the most famous Varangians and, later on, the Norwegian king. Based on Old Norse and Latin sources as well as the Primary Chronicle, this article discusses the beginning of Haraldr’s long-term stay abroad, when, after the battle of Stiklestad, he sought refuge at the court of the Rus’ prince Yaroslav the Wise. Being aware of the convention characteristic of the saga narrative, the author outlines the political context behind the friendly reception that 15-year-old Haraldr and his companions received in Novgorod. The primary focus of the article is Haraldr’s participation in the Rus’ campaign against Poland that took place soon after he entered into the service of Yaroslav the Wise. Although there are several major research works in the Polish historiography concerning the crisis of the Polish state in the 1030s, they omit or merely touch upon Haraldr’s role in these events. Taking the Old Norse sources (including skaldic poetry) into consideration casts new light on the campaign. It seems that the Rus’ expedition was led along the main waterways linking the core parts of 11th-century Poland with Kiev, and that the decisive battle took place in Kuyavia or Mazovia. Although the Old Norse sources underline Haraldr’s role in achieving victory, the part he played in these events cannot be overestimated. Haraldr was young and inexperienced but still an important political figure. Yaroslav therefore seems to have provided him with Eilífr, son of Rǫgnvaldr Úlfsson, under whose guidance he could develop his own skills and authority – the campaign against Poland was a suitable occasion to do that.